2023
DOI: 10.1101/2023.11.02.564926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotype combinations drive variability in the microbiome configuration of the rhizosphere of Maize/Bean intercropping system

Giovanna Lanzavecchia,
Giulia Frascarelli,
Lorenzo Rocchetti
et al.

Abstract: In intercropping system, the interplay between cereals and legumes, which is strongly driven by complementarity of below-ground structures and their interactions with the soil microbiome, raises a fundamental query: Can different genotypes alter the configuration of the rhizosphere microbial communities? To address this issue, we conducted a field study, probing the effects of intercropping and diverse maize (Zea maysL.) and beans (Phaseolus vulgarisL.,Phaseolus coccineusL.) genotype combinations. Our results … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…The methanol‐enriched wheat rhizosphere soils exclusively contained MAGs identified as Gemmatimonadales , Roseimicrobium and Nitrososphaeraceae . This supports the prior identification of a greater diversity of these specific taxa in the methanol‐enriched rhizosphere soils relative to the unplanted soils (Macey et al, 2020 ), with many of the taxa previously identified as enriched in rhizosphere soils (e.g., Chthoniobacter [Sangwan et al, 2004 ], Nitrososphaeraceae [Prudence et al, 2021 ], Methylophilaceae [Kanukollu et al, 2022 ; Macey et al, 2020 ], and species within the Acidobacteriota and Verrucomicrobiota [Da Rocha et al, 2013 ; Lanzavecchia et al, 2024 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The methanol‐enriched wheat rhizosphere soils exclusively contained MAGs identified as Gemmatimonadales , Roseimicrobium and Nitrososphaeraceae . This supports the prior identification of a greater diversity of these specific taxa in the methanol‐enriched rhizosphere soils relative to the unplanted soils (Macey et al, 2020 ), with many of the taxa previously identified as enriched in rhizosphere soils (e.g., Chthoniobacter [Sangwan et al, 2004 ], Nitrososphaeraceae [Prudence et al, 2021 ], Methylophilaceae [Kanukollu et al, 2022 ; Macey et al, 2020 ], and species within the Acidobacteriota and Verrucomicrobiota [Da Rocha et al, 2013 ; Lanzavecchia et al, 2024 ]).…”
Section: Resultsmentioning
confidence: 99%